Penggunaan Nama Tanpa Izin Yang Merugikan Hak Moralitas Pencipta Dalam Karya Cover Lagu Pada Platfrom Digital - Wiwin Wintarsih Windiantina (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The swift growth of digital technology for music sharing via online platforms has resulted in a notable rise in the production and spread of cover songs. However, these activities often lack appropriate recognition of the original songwriters in the public metadata. This situation brings about legal challenges regarding the safeguarding of both moral and economic rights for creators as outlined in Law Number 28 of 2014 on Copyright, especially in Articles 5 and 9. From a normative perspective, the law ensures protection for creators, including their right to be recognized as the originators of their creations and their right to earn financial rewards from them. Nevertheless, in actual practice, there are still inconsistencies, as cover songs available on digital services frequently only acknowledge the artist or group performing the song, failing to clearly credit the original songwriter. This issue is evident in the song Akad, which was made famous by Payung Teduh and authored by Is (Muhammad Istiqamah Djamad), where several cover renditions do not consistently include the songwriter's name. The purpose of this research is to evaluate the gap between legal standards and the actual practices surrounding the attribution of songwriters in cover versions on digital platforms, along with the legal consequences for safeguarding moral and economic rights. The research employs an empirical legal approach, utilizing both legislative and case studies. The results show that errors in metadata, particularly the lack of acknowledgment for the songwriter in cover versions, could infringe upon both the moral and economic rights of the creator. As a result, enhanced monitoring and a more engaged role from digital platforms are essential to ensure accurate metadata and to provide adequate legal protection.